System Reliability for Jacket Platform Subjected to Wave and Current Loads - ., VJ Kurian, Zafarullah Nizamani, MS Liew, MMA Wahab (2012)
Codes applicable to Jacket platforms such as API WSD, API LRFD and ISO 19902, are based on component and joint reliability design. They consider overall structural integrity, redundancy and multiple failure paths only indirectly by using structural integrity assessment methods. Failure of a single component does not mean that the capacity of platform has reached the limit and hence for the reassessment of old platforms component based approach becomes unviable.